High‐Altitude Closed Magnetic Loops at Mars Observed by MAVEN. Issue 22 (18th November 2017) - Xu, Shaosui; Mitchell, David; Luhmann, Janet; Ma, Yingjuan; Fang, Xiaohua; Harada, Yuki; Hara, Takuya; Brain, David; Weber, Tristan; Mazelle, Christian; DiBraccio, Gina A.
Abstract: With electron and magnetic field data obtained by the Mars Atmosphere and Volatile EvolutioN (MAVEN) spacecraft, we have identified closed magnetic field lines, with both foot points embedded in the dayside ionosphere, extending up to 6, 200 km altitude into the Martian tail. This topology is deduced from photoelectrons produced in the dayside ionosphere being observed traveling both parallel and antiparallel to the magnetic field. At trapped‐zone pitch angles (within a range centered on 90° where electrons magnetically reflect before interacting with the atmosphere), cases with either solar wind electrons or photoelectrons have been found, indicating different formation mechanisms for these closed loops. These large closed loops are present in MHD simulations. The case with field‐aligned photoelectrons mixed with solar wind electrons having trapped‐zone pitch angles is likely to be associated with reconnection, while the case with photoelectrons at all pitch angles is probably due to closed field lines being pulled tailward by the surrounding plasma flow. By utilizing an algorithm for distinguishing photoelectrons from solar wind electrons in pitch angle‐resolved energy spectra, we systematically map the spatial distribution and occurrence rate of these closed magnetic loops over the region sampled by the MAVEN orbit. We find that the occurrence rate ranges from a few percent to a few tens of percent outside of the optical shadow and less than one percent within the shadow. These observations can be used to investigate the general magnetic topology in the tail, which is relevant to cold ion escape, reconnection, and flux ropes. Key Points: Two types of thousand‐kilometer closed magnetic loops are identified in the Martian tail for the first time The occurrence rate of these closed loops is determined to range from a few tenths to a few tens percent These observations improve our understandings of Mars tail magnetic topology, cold ion escape, and reconnection